Design and Analysis of Ultrawide Band Microstrip Antenna with Band-Notched Characteristics - Singh, Navtej (My University, 2015)
In the present day scenario of growing wireless communications, demand for compact, low-profile, ultrawide band (UWB), multiple functionality, pure polarization, and low cost antennas have arisen remarkably. Due to which, research studies in the field of microstrip patch antennas have drastically increased in the past few years. For short range and high data rate applications, wireless systems require ultrawide band microstrip antennas which operate in the frequency band of 3.1 to 10.6 GHz. But in the UWB frequency band there are some other frequency bands such as WLAN, WiMAX, C band etc. These bands can cause interference with the UWB band. Several techniques have been developed to avoid the inference from these bands. In this report, design and analysis of two UWB microstrip antennas with notched band characteristics are presented. The first design consists of a semi-circular disc with a dual stepped triangular patch. Also, a slot in the shape of a circular arc is cut on the circular patch which generates a notched band from 4.8 to 6.2 GHz for WLAN band. The antenna operates at an ultrawide frequency band of 9.7 GHz ranges from 2.8 to 12.5 GHz. Maximum gain of the antenna is 5.3 dB. The second antenna design has dual notched band characteristics. It consists of a mirrored E-shaped structure inscribed inside a circular ring radiator. This E-shaped structure creates a stop band at 3.12 to 3.88 GHz to avoid interference from WiMAX band with center frequency 3.5 GHz. Trapezoidal shaped ground plane having a semicircular notch is used to enhance the bandwidth of the antenna. The impedance bandwidth of the antenna ranges from 2.7 to 11.95 GHz which covers the UWB frequency range. To create a second notch band, an H-shaped parasitic element is etched above the ground plane on the bottom side of the antenna. This element creates a stop band at 4.78 to 5.48 GHz to avoid interference from WLAN band (5.15 to 5.825 GHz). Fabricated design and the measured results of the antenna are also shown in this report.
ME, ECED
Keywords: Band Notch; Micro strip antenna; Circular patch; Ultra wide-band; ECED